Serological diagnosis of HIV infection: incidence, outcome and significance of partial reactions found in western blot analysis. - Lantin, J P (1989)
Between May 1986 and April 1987 routine screening for anti-HIV antibody was performed by enzyme immunoassay (EIA) on 3344 serum samples. The 1160 samples found positive or borderline were further analysed in Western blot (Wb). We analysed the frequency of different patterns of 'intermediate' Wb reactions (1-3 'specific' bands) and tried to determine their significance by searching for possible modifications of the pattern of reaction a few months later. Of 1160 Wb, 461 were clearly positive, 489 negative and 210 'intermediate'. The latter consisted of: 92 sera with anti-p24 (associated or not), 23 with anti-gp 120 and 160, 16 with anti-p55, 12 with anti-p41, 10 with anti-p65, eight with anti-p17 and four with anti-p31. A non-specific pattern was observed in the remaining 45. Of these sera, 46% were obtained from high risk subjects, 38% from persons without risk and in 16% no reliable information was available. In 30 subjects (24 with p24 and 6 with p41), a second sample was obtained about three months later. The reaction persisted in nine, was replaced by another in five, and disappeared in 15. One subject with anti-p41 in the first sample became clearly positive. In one of the 15 samples with disappearance of the reaction, the antigen p24 was present as the only sign of HIV infection. Later samples of this subject showed clear seroconversion. In many subjects with and without risk of exposure to HIV, the Wb gives an intermediate pattern of reactions (1-3 specific bands), that does not permit definitive conclusion on one single sample. Later controls are therefore necessary. Most of these reactions do not correspond to HIV infection.